PREPARING A DATA BASE FOR ESTIMATING SEISMIC DAMAGE ON BUILDINGS BY APPLYING ANN - Peško, Igor; Dražić, Jasmina; Mučenski, Vladimir; Trivunić, Milan (Journal of Applied Engineering Science, 2012)
Seismic risk in urban areas increases over time, so the research projects on all the aspects of seismic safety carried out currently are numerous. In order to plan preventive measures, the estimation of possible damages on buildings plays a significant role. This paper describes preparation of a data base for predicting seismic damage category by applying artificial neural networks (ANN). The base will be defined relying upon the available data from the reports after the earthquake in Kraljevo (03/11/2010). Key words earthquake, damage, data base, artificial neural networks